Executive Committee Minutes 2019-12-05 - Academic Senate:::::::::
Agenda – Approved. Minutes of 11/14/19 – Approved. President Report. Provost Report. Vice Chair Report. Vice President for Student Affairs Report. Associated Students Report. From EPC: BA Global Studies revision – approved for Senate consent calendar. Discussion of 2020 Faculty Retreat. Meet with Superlative Group – CSU/Corporate Partnerships. APARC Report. EPC Report. Request to Present CSU/Elsevier negotiations to Senate – approved as special report for the Senate. FSAC Report. SAC Report. Occasional Lecturers Report. Senate Agenda approved.